PENINGKATAN PERANAN NEGARA DALAM SISTEM PEREKONOMIAN INDONESIA - Fathurrahman Fathurrahman (Valid: Jurnal Ilmiah, 2016)
Economic system in the world can be grouped into three namely the capitalist economic system, socialist economic system and a mixed economic system. The capitalist economic system provides sizeable opportunity and freedom to individual economic actors to engage in bestinterests of the individual, including factors of production and resources. While the socialist economic system does not provide / restrict the freedom of individuals to production factors and resources; and a system of remuneration based on the role and functioning of society / social. The development of the current economic system, each system is difficult to apply in a pure, it is happening is a situation where the influence of other systems can not be avoided. So that the capitalist system which applied a country there are various issues socialist and the socialist system there are elements of capitalism. Berdasarkan these differences, the Indonesian economic system is known as a mixed system, where in the organization of the economic system that is applied are combined elements of capitalist and socialist. Indonesia Economic System that is known as Pancasila Economic Openness has been up and running with a variety of results that have been achieved. The system is extremely necessary to be improved in order to realize what dharapkan nation of Indonesia as defined in the preamble of the Constitution 45, described in chapter-fasalnya and additional amendments. Indonesia's economic system is geared to the realization of a just and prosperous society in accordance preamble 45 elaborated on the provisions contained in the articles, namely 33, 23, 27, and 34 Constitution 45